Clinical evaluation, management and outcome of hollow viscus perforations - T., Anjaneya; H. V., Vilas Crithic (International Surgery Journal, 2019)
Background: Gastrointestinal perforation is the third most common cause for exploratory laparotomy as an emergency. With the advent of drugs against acid peptic disease the incidence of peptic ulcer perforations is on decline. The advent of laparoscopy and endoscopy has played decisive role in the diagnosis and management of gastric and colorectal perforations. Aim of the study is to study the clinical outcome, surgical management and postoperative complication of peritonitis secondary to hollow viscus perforation. Methods: This was prospective study of 50 cases. All patients admitted and treated with perforation secondary to Hollow viscus perforations in surgical wards of M S Ramaiah Medical College, Bangalore, during the period of April 2016 to October 2017. Patients with peritonitis secondary to hollow viscus perforation admitted was evaluated and the diagnosis was made. Results: Out of 50 patients, most were male patients between 30-50 years age group. Duodenal ulcer perforation led the list. 4 were gastric, 37 were duodenal, 3 were jejunal, 6 cases were ileal. However colonic perforations were not observed. Wound infection leads the list of postoperative complications with faecal leak and burst abdomen following residual abscess. Almost all perforations were treated surgically. Conclusions: It was thought that with the introduction of better H2 receptor blockers and proton pump inhibitors, incidence of peptic perforations would decrease. Early recognition of perforations, prompt surgical intervention, adequate drainage, recognition of co-morbid conditions and complications would help in reduction of morbidity and mortality.